Handlungsorientierter Unterricht an beruflichen Schulen in Bayern - Roche, Jörg-Matthias [Verfasser]; Terrasi-Haufe, Elisabetta [Verfasser] (My University, 2017)
"In times of globalization and the increasing importance of media, instruction in vocational schools is changing dramatically. This is also true for dual-stream vocational schools in Germany comprising both general education as well as job-specific, vocational education and on-the-job-training. Young adults attending such schools - regardless of whether or not they have any (recent) migration background - all are in need of focused attention on language competencies in general and focused attention on professional language skills and languages for special purposes in particular. The paper presents the foundations and leading principles of a new concept which entails pedagogical, curricular and administrative aspects: Berufssprache Deutsch (German for Professional Purposes). The concept is based on a pragma-linguistic notion of communication (doing things with words) and a constructivist and constructionist notion of learning and language acquisition. The paper also presents the parameters of a new curriculum grounded on pragmatic principles as well as appropriate teaching materials for integrative approaches to language acquisition/teaching on and for the job." (Authors abstract ; BIBB-Doku)
Keywords: L 1.6.1 Deutsch; S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; L 2.1 Lernformen; I 2.1.2.3 Bayern; Sprachförderung; Deutschunterricht; Berufsschule; Handlungsorientierter Unterricht; Unterrichtsmaterial; Bayern